(untitled) (Revista de Ciências Agroveterinárias, 2018)
The aim of this study was to assess the behavior of morphological components and yield of simple hybrid corn grains cultivated in different environments. Three field trials were conducted in the state of Rio Grande do Sul under an experimental randomized block design with factorial treatment: seven (simple hybrids) x three (cultivation environments) arranged in three replications. The analysis of variance showed significant interaction between genotype and environment for the traits ear diameter, number of kernels per row, cob diameter, grain mass per ear and grain yield. The number of grains per rows and thousand-grain weights were not influenced by environments, being intrinsic characteristics of each genotype. The length of the cob presents similar among the hybrids, being influenced only by the cultivation environment. The plant height and prolificacy were higher in Vista Gaúcha, RS, however, Tenente Portela, RS, had a higher ear insertion height, grain number per row, ear mass, grain mass per ear and grain yield. Hybrids DKB 290 PRO 3® and DKB 315 PRO 3® presented the highest yields in the average of the environments studied.